Model of family therapy in practice: Social workers' perspective - Chan, Cheong Chong (2014)
Transgenerational, Structural, Strategic and Milan models are four popular models of family therapy.The application of these models in Asian families has been widely discussed by various practitioners and academic scholars.This paper investigates the application of models of family therapy in the Singapore context.Two social workers who have formal training and practices in family therapy were interviewed.The investigation focuses on the sequence of the family therapy sessions, cross-cultural issues, techniques and orientations used by the social workers.The interviews show that the Milan and Strategic models are two most dominant models in practicing family therapy.Besides that, Systemic theory has been found to be the most influential framework for both social workers in conducting family conferences.